Novel staphylococcal inhibitors of neutrophil granule enzymes - Ploscariu, Nicoleta Teodora (Kansas State University, 2018)
Neutrophils are our most abundant white blood cells and the first leukocytes to infiltrate sites of infection or damaged/healing tissue. Activation of neutrophils results in the mobilization of several types of granules stored within their cytosol, such as the so-called azurophilic granules, which either fuse with the maturing endophagocytic compartment or are released into the extracellular environment. One of the most abundant component of zurophilic granules is a heme-containing enzyme called myeloperoxidase (MPO), which reduces the H₂O₂ produced by the neutrophil’s respiratory burst to generate cytotoxic hypohalous acids, most typically HOCl. While neutrophil granule enzymes are essential for our innate defenses, neutrophil-driven inflammation outside this beneficial context lies at the heart of many non-infectious human diseases. Staphylococcus aureus and closely related species are highly adapted to their hosts and have evolved many strategies to resist opsonization and phagocytosis. S. aureus shows resistance to killing following uptake into the phagosome, which suggests that the bacterium can actively evade specific intracellular killing mechanisms used by neutrophils. Recent work found a highly conserved S. aureus protein, SPIN (for Staphylococcal Peroxidase INhibitor), that specifically binds and inhibits MPO [1]. This study was focused on characterizing the structure/function relationship for MPO inhibitors, SPIN proteins. To identify key residues for SPIN function in more detail, we examined two types of SPIN proteins using structural methods, direct binding assays, and functional assays for MPO activity: deletion mutants and SPIN proteins originating from divergent staphylococcal species. Together, these studies shed light on the molecular features which determine the specificity of SPIN proteins for MPO and suggest potential avenues for using this information toward the design of synthetic MPO inhibitors. In addition to the focus on targeted inhibition of MPO for its therapeutic value in treatment of a number of significant human inflammatory diseases, our investigations contributed in expanding our knowledge on infection spreading. As a first cellular host defense response, the neutrophil interaction with pathogens are of major interest. Characterization of staphylococcal immune evasion proteins is vital for understanding bacterial survival when encountering neutrophils and their bioactive constituents.
Keywords: Inhibitor; Staphylococcus aureus; Staphylococcus delphini; Immune Evasion; X-ray CrystallographyMyeloperoxidase